2005
DOI: 10.2307/3473312
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Mating Systems and Parental Conflict as a Barrier to Hybridization in Flowering Plants

Abstract: Parental conflicts can lead to antagonistic coevolution of the sexes and of parental genomes. Within a population, the resulting antagonistic effects should balance, but crosses between populations can reveal conflict. Parental conflict is less intense in selfpollinating plants than in outcrossers because outcrossing plants are pollinated by multiple pollen donors unrelated to the seed parent, while a self-pollinating plant is primarily pollinated by one individual (itself). Therefore, in crosses between plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 27 publications
9
58
2
Order By: Relevance
“…Some viable seeds (60%) are produced in the reciprocal cross, but these are small due to early endosperm cellularization (Rebernig et al, 2015). C. rubella is a self-fertilizing species and C. grandiflora is an outcrossing species, which may be related to the lack of completely reciprocal phenotypes (Brandvain and Haig, 2005;Rebernig et al, 2015). Similar phenotypes have been observed in rice interspecific crosses (Ishikawa et al, 2011), although in these instances the resultant seeds are larger or smaller than seeds from intraspecific crosses, rather than aborted.…”
Section: Imprinting and Interspecies Or Interploidy Hybrid Seed Phenomentioning
confidence: 83%
“…Some viable seeds (60%) are produced in the reciprocal cross, but these are small due to early endosperm cellularization (Rebernig et al, 2015). C. rubella is a self-fertilizing species and C. grandiflora is an outcrossing species, which may be related to the lack of completely reciprocal phenotypes (Brandvain and Haig, 2005;Rebernig et al, 2015). Similar phenotypes have been observed in rice interspecific crosses (Ishikawa et al, 2011), although in these instances the resultant seeds are larger or smaller than seeds from intraspecific crosses, rather than aborted.…”
Section: Imprinting and Interspecies Or Interploidy Hybrid Seed Phenomentioning
confidence: 83%
“…A possible reason is that in the sexual conflict between pollen and maternal genomes during provisioning of the seed, the pollen genotype derived from the inbreeder is less able to elicit resources from the outbreeding maternal genome than vice versa (Wright et al, 2008). This phenomenon has been noted as a possible barrier to hybridization in a range of other plant genera (Brandvain and Haig, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, divergence in mating system could explain why multiple imprinted loci exhibit coordinated effects in hybrid seeds. A literature review of crosses between outcrossing and self-fertilizing plants found features of paternal excess when outcrossers were fathers but maternal excess when outcrossers were mothers (Brandvain & Haig 2005 (Josefsson et al 2006;Walia et al 2009). The 'differential-dosage' hypothesis proposes that many mechanisms, not just imprinted expression, cause parental effects in seed development (Dilkes & Comai 2004).…”
Section: Interspecific Crossesmentioning
confidence: 99%